Dampak Implementasi Realisasi Anggaran Program Kesehatan Terhadap Kepuasan Masyarakat Desa Pantai Linuh Kabupaten Tanah Laut - Alfida Laila Nor; Hikmahwati; Rizky Amelia (P3M Politeknik Negeri Banjarmasin, 2026)
This study aims to analyze the impact of health program budget realization on community satisfaction with Posyandu services in Pantai Linuh Village, Tanah Laut Regency. A descriptive quantitative approach was employed involving 70 Posyandu service users selected through total sampling. Data were collected using a questionnaire developed based on the nine dimensions of the Community Satisfaction Index (CSI) regulated by the Indonesian Ministry of Administrative and Bureaucratic Reform Regulation No. 14 of 2017, supported by observations, interviews, and documentation of the 2022–2024 budget realization reports. The findings indicate that the realization of the health program budget exceeded 95% in both 2023 and 2024. However, community satisfaction was not evenly distributed across all service dimensions. The dimensions of service requirements, procedures, and service costs were rated as satisfactory, while service timeliness, service output, staff competence, staff behavior, facilities and infrastructure, and complaint handling were rated as moderately satisfactory. The novelty of this study lies in integrating village budget realization evaluation with service quality assessment through the Community Satisfaction Index in community-based health services. This study contributes to the public sector accounting and public service literature by demonstrating that the effectiveness of village health programs should be assessed not only through budget absorption but also through the quality of services perceived by beneficiaries